Physical Fractionation of Oilseed Rape Oleosomes - Bramante, Filippo (2024)
Oleosomes (oil bodies) are natural oil droplets, sub-cellular organelles present in oleaginous plant seeds, that act as energy stores for seed germination. Oleosomes can be recovered from seeds by a wet milling process. These natural oil droplets are surrounded and stabilised by a multicomponent interface of phospholipids and specific proteins (mainly oleosins) unique to oleosomes. This interface could be employed as a natural emulsifier if separated from the oil. Freeze-thawing was used for the first time as a technique to rupture oleosomes recovered from oleaginous seeds, effectively dismantling these organelles, separating them into surface material and bulk oil. The aim of this work was to pioneer a physical method (freeze-thawing) to separate the oleosome multicomponent interfacial (hemi-membrane) material from the bulk oil and to establish the nature and properties of both fractions. Objectives: 1 Test a range of freeze-thawing conditions for their ability to rupture oleosomes 2 Establish the mechanism that explains the rupture of oleosomes under freeze-thawing conditions 3 Separate oleosome fractions formed after freeze-thawing and establish their properties and nature 4 Explore if there might be a connection between oleosome composition and their tendency to rupture on freeze-thawing Oleosomes were recovered from oilseed rape seeds by extraction in NaHCO3 0.1M, and a dispersion of oleosomes (an oil-in-water emulsion with an average of 72% dispersed phase fraction) at pH 9 was obtained. These oleosome emulsions were frozen (-20°C) and thawed (20°C), and their freeze-thaw stability assessed in terms of amount of oil recovered from ruptured oleosomes. The aqueous phase crystallised upon cooling the emulsion from 5°C to -20°C, whereas lipid crystallisation in the droplets occurred between two and hours at -20°C. Under these conditions oleosome rupture occurred concurrently with lipid crystallisation; increasing the duration of the isothermal hold at -20°C led to increased oil recovery. On lowering the freezing temperature to -75°C or below, oleosome lipids crystallised rapidly, and oleosomes remained intact on thawing. For emulsions frozen at -20°C, reducing the original pH value to 6 or 3 promoted oleosome freeze-thaw rupture, especially at pH 3, a pH at which oleosomes were ruptured within 2 min, during the cooling step. Heat treating oleosome emulsions at 95°C for 7 min before freeze-thawing appears to be another way of promoting oleosome rupture at this relatively ‘soft’ freezing temperature (-10°C) where water molecules in the continuous phase, but not the triacylglycerol (TAG) molecules in the oleosome, freeze. By increasing the emulsion continuous phase fraction from 0.28 (w/w) to 0.50 (w/w) seemed to have a protective effect on oleosomes, as no oil was recovered after freeze-thawing (freezing at -20°C for 24 h), although oil released was visible by the naked eye. Increasing the number of freeze-thawing cycles led to a marginal increase of oleosome destabilisation. After freeze-thawing and oil recovery from the oleosome emulsion, the remnant oleosome material was dispersed in buffer and centrifuged to recover the interfacial material from ruptured oleosomes. The supernatant produced by centrifugation mainly contained the oleosome interfacial material; moreover, a sedimented material containing oil probably stabilised by interfacial material and the remaining storage protein was obtained. The supernatant and sedimented fractions were both tested for their emulsifying capacity. The emulsions generated were unstable to creaming due to their high continuous phase fraction, but remained stable to coalescence (no change in particle size distribution) over a 14 day-storage period at 5°C. The oil recovered from the freeze-thawed and centrifuged oleosome emulsions was devoid of phospholipids (contaminants for oils) and had an oxidative status comparable to that of fresh oils. The oil released during oleosome rupture therefore appears to be of similar quality to refined oils: this observation could act as a significant industrial driver to adopt oleosome recovery and rupture as a means of ‘extracting’ oil and ‘manufacturing’ a natural multicomponent surface-active material with a range of industrial applications. Oleosomes from different oilseed rape varieties had different lipid compositions and different tendencies to rupture on freeze-thawing; a simple correlation between oleosome lipid composition and tendency to rupture was not established. In fact, whilst the oil composition has an important impact on the droplet crystallisation behaviour, the physical stability of the oleosomes may be affected by the interfacial composition (phospholipids - PLs - but also other components such as sterols), which does not easily correlate with the oil composition. From the work reported in this thesis the rupture of oleosomes by freeze thawing is affected by several variables suggesting that a range of factors can lead to the weakening of the interface of oleosomes. The significant stimulation of oleosome rupture by low pH suggests that changes to interfacial protein conformation can lead to oleosome rupture. If these changes were reversible then using a low pH in the process would be expedient, however if not, then the functionality of the released multicomponent hemi-membrane material would be compromised. What is clear is that under neutral to alkaline conditions freezing oleosomes at relatively slow rates to a level that allows lipids to crystallise results in oleosome rupture on thawing. More rapid cooling of oleosomes by plunging the emulsions to very low temperatures (-75°C or lower) does not lead to oleosome rupture unless the system is taken ‘up’ to higher temperatures (-20°C). This raises more questions about the nature of the lipid crystals in oleosomes and how they differ under these conditions, and whether they themselves are responsible for the rupture of oleosomes or if changes to the surface proteins during these significant temperature changes also play a role.